Gry patriotyczne w II połowie XIX i na początku XX wieku na przykładzie gry „Piast” - Kabacińska-Łuczak, Katarzyna (Studia Edukacyjne, 2020)
Patriotic games in the second half of the nineteenth and early twentieth centuries were not only a ludic function, but also an educational function. Games that convey knowledge in the field of literature and national history, as well as geographical locations, were to shape the attitudes of patriotism, love for the country. For the propagation of Polishness in the era of partitions, the family was primarily responsible, and games were used as a help in forming patriotic attitudes in home education.